Health-care cost of diabetes in South India: A cost of illness study - Sadanandam Akari; Uday Venkat Mateti; Buchi Reddy Kunduru (Wolters Kluwer Medknow Publications, 2013)
Objective: The objective of this study is to analyze the health-care cost by calculating the direct and indirect costs of diabetes with co-morbidities in south India. Methods: A prospective observational study was conducted at Rohini super specialty hospital (India). Patient data as well as cost details were collected from the patients for a period of 6 months. The study was approved by the hospital committee prior to the study. The diabetic patients of age >18 years, either gender were included in the study. The collected data was analyzed for the average cost incurred in treating the diabetic patients and was calculated based on the total amount spent by the patients to that of total number of patients. Findings: A total of 150 patients were enrolled during the study period. The average costs per diabetic patient with and without co-morbidities were found to be United States dollar (USD) 314.15 and USD 29.91, respectively. The average cost for those with diabetic complications was USD 125.01 for macrovascular complications, USD 90.43 for microvascular complications and USD 142.01 for other infections. Out of USD 314.15, the average total direct medical cost was USD 290.04, the average direct non-medical cost was USD 3.75 and the average total indirect cost was USD 20.34. Conclusion: Our study results revealed that more economic burden was found in male patients (USD 332.06), age group of 51-60 years (USD 353.55) and the patients bearing macrovascular complications (USD 142.01). This information can be a model for future studies of economic evaluations and outcomes research.